Optical Methods in Sensing and Imaging for Medical and Biological Applications - Dragan Indjin (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The recent advances in optical sources and detectors have opened up new opportunities for sensing and imaging techniques which can be successfully used in biomedical and healthcare applications. This book, entitled 'Optical Methods in Sensing and Imaging for Medical and Biological Applications', focuses on various aspects of the research and development related to these areas. The book will be a valuable source of information presenting the recent advances in optical methods and novel techniques, as well as their applications in the fields of biomedicine and healthcare, to anyone interested in this subject.